Country size bias in global health: cross-country comparison of malaria policy and foreign aid - Jezek, Tomas (Global health research and policy, 2021)
BACKGROUND: Foreign aid has been shown to be favourably biased towards small countries. This study investigated whether country size bias also occurs in national malaria policy and development assistance from international agencies. METHODS: Data from publicly available sources were collected with countries as observational units. The exploratory data analysis was based on the conceptual framework with socio-economic, environmental and institutional parameters. The strength of relationships was estimated by the Pearson and polychoric correlation coefficients. The correlation matrix was explored by factor analysis. RESULTS: Malaria burden is strongly correlated with GDP per capita, total health expenditure per capita, HDI; moderately with latitude, weakly with elevation, urban population share, per capita funding from the Global Fund, PMI USAID, UK government and UNICEF. Small country status is strongly correlated with population size, land area, island status; moderately with development assistance received per capita, weakly with funding per capita from Global Fund, government NMP and PMI USAID. Policy score 1, a variable derived from our factor analysis and related to malaria endemicity, is significantly strongly correlated with the malaria burden, moderately with HDI, GDP per capita, total health expenditure per capita, PMI USAID funding; weakly with island status, urban population share, latitude, coastal population share, total government expenditure and trade openness, Global Fund funding, World Bank funding, UK government funding, and UNICEF funding per capita. Policy score 2, which captures variation not related to malaria endemicity, is significantly weakly related to the ICRG index, PMI USAID funding per capita and small country status. CONCLUSIONS: The results suggest that malaria burden and economic development are bidirectionally related. Economic development can contribute to a reduction in the malaria burden. Country size does not negatively impact malaria burden, but it does account for greater development assistance per capita from selected international agencies. National malaria policy is associated with parameters related to public governance and is modified in small countries. Small country bias is present in the distribution of socio-economic resources and the allocation of foreign aid. Small countries are characterized by distinct environmental and socio-political properties.
Keywords: International agencies; International Cooperation; Cost of Illness; malárie; Health Policy; Malaria; osobní újma zaviněná nemocí; Global Health; Global health; Humans; celosvětové zdraví; Global burden of disease; Health care economics and organizations; Endemic diseases; lidé; zdravotní politika; mezinárodní spolupráce; Environment and public health